Risk Analysis Of Disorders Due To Isoflurane Exposure Among Healthcare Workers In The Operating Room: A Case Study At Ananda Women And Children Hospital - Kaisar Razak; Hairuddin K; Jangga, Jangga (Jurnal EduHealth, 2024)
Isoflurane is an inhalation anesthetic agent commonly used in clinical practice for the induction and maintenance of general anesthesia. Isoflurane has a depressant effect on the central nervous system, working by increasing the activation of inhibitory GABA receptors and reducing excitatory synaptic transmission. One of the key factors affecting the level of isoflurane exposure in the operating room is the room ventilation and air filtration system. Poor ventilation in the operating room can cause the concentration of anesthetic gases, such as isoflurane, to accumulate in the air, increasing the risk of exposure to health workers. Ineffective or inadequate ventilation systems may not be able to remove anesthetic gases released during surgical procedures, which can ultimately result in isoflurane exposure at hazardous levels. The purpose of this study was to identify and analyze the risk of health problems due to isoflurane exposure and to develop effective risk management to minimize the impact of isoflurane exposure on health workers in the operating room of RSIA Ananda and to analyze the existing operating room standards in the operating room of RSIA Ananda. The type of research that will be used in this study is quantitative research using a cross-sectional design. This study was conducted in the Operating Room of Ananda Mother and Child Hospital, Makassar from October to November 2024. The population and sample were all health workers on duty in the operating room of Ananda Mother and Child Hospital, which was 45 health workers. The results of this study indicate that of the 45 respondents who always use PPE and experience health problems such as nausea, which is 62.5% and with a P Value of 0.0612> 0.05, have never been exposed to isoflurane and experience nausea as much as 37.5% with a P Value of 0.030 <0.05, health workers who have worked for 1-5 years have a higher percentage of nausea, which is 66.7% with a P Value of 0.066> 0.05. While the age group 25-34 years as many as 70.8% experience nausea with a P Value of 0.0590> 0.05. The conclusion of the statistical analysis shows a significant relationship between the duration of isoflurane exposure and health problems in health workers, while the use of PPE, age and length of work do not have a significant relationship.